Tuning into Learning: How Mini Podcasts Spark Focus, Dialogue, and Independence in Thematic Classrooms - Ach. Nurfuad Al-Fajri; Maulida Eka Syaputri; Miftahus Surur; Siti Farian (Al-Qalam Institute, 2025)
This study aims to explore how mini podcasts are used as thematic learning media in grades 4–6 of elementary school, as well as their impact on learning attention, class discussions, and student independence. Using a qualitative approach with a case study design, data were collected through semi-structured interviews, learning documentation, and field observations at MI Bustanul Ulum 01. The analysis was carried out thematically using the Miles and Huberman model, which included data reduction, data presentation, and conclusion. The results of the study show that mini podcasts can increase students' initial focus, create a conducive learning atmosphere, and strengthen material retention. Additionally, these media encourage active participation in thematic discussions and enable students to learn independently outside of class hours. The study's implications suggest that mini podcasts are an effective alternative medium relevant for application in elementary schools, particularly in areas with technological limitations. These findings make an empirical and practical contribution to the development of audio learning media that is contextual and integrated with thematic approaches.